دراسة العلاقة بين مكونات النّمو السّكاني و مؤشرات التّنمية البشريّة في سورية خلال الفترة من عام 2000إلى عام .2012 - طويل, دانيا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
While the human is based rule for communities building and doing all development plans (population are producers and consumers) , this essay put a goal to study the impact of changes of population number on their ability to achieve human development. By using stepwise regression to study analyze and identify the impact of changed rates on population growth components (birth, death and migration) on human development indicators (health index- education index-individual income index). The searcher found a set of results demonstrated the existence of a positive significant relationship between rates of population growth components and both indexes health and education, on the other hand, the results proved the existence of a negative significant relationship between rates of population growth components and individual income index . يعد الإنسان القاعدة الأساسية لبناء المجتمعات، وتقع على عاتقه مهمة القيام بكل الخطط التنموية و تنفيذها، فالسكان هم المنتجون وهم المستهلكون، و انطلاقاً من ذلك هدف هذا البحث لدراسة أثر التغيرات في أعداد السكان في قدرتهم على تحقيق التنمية البشرية. من خلال استخدام أسلوب تحليل الانحدار المتعدد لدراسة و تحليل و من ثم تحديد أثر تغير مكونات النمو السكاني (معدل الولادات، معدلات الوفيات الخام، معدل صافي الهجرة) على مؤشرات التنمية البشرية (مؤشر الصحة ، مؤشر التعليم، مؤشر الدخل الفردي). توصل الباحث إلى مجموعة من النتائج التي أثبتت وجود علاقة معنوية ذات طبيعة طردية بين تغيرات مكونات النمو السكاني(معدل الولادات، معدلات الوفيات الخام، معدل صافي الهجرة) وتغيرات كلٍّ من مؤشري الصحة والتعليم في سورية خلال فترة الدراسة، كما أثبتت وجود علاقة معنوية ذات طبيعة عكسية بين مكونات النمو السكاني و مؤشر الدخل الفردي.